ON THE ISSUE OF PREVENTION IN PEDIATRIC DENTISTRY - Tulanova Moxichehra Akram kizi (Western European Studies, 2023)
The best form of prevention of dental diseases in children and adolescents is medical examination. It includes planned sanitation of the oral cavity and is carried out simultaneously with the treatment of concomitant diseases. High-quality medical examination allows you to prevent the development of complicated forms of caries, loss of permanent teeth, the development of dental deformities and, as a result, diseases of internal organs and systems
Keywords: Pediatric dentistry; teeth; modern technology; treatment